Recent Advances in the Development of Semiconducting DPP‐Containing Polymers for Transistor Applications. (25th September 2012) - Nielsen, Christian B.; Turbiez, Mathieu; McCulloch, Iain
Abstract This progress report summarizes the numerous DPP‐containing polymers recently developed for field‐effect transistor applications including diphenyl‐DPP and dithienyl‐DPP‐based polymers as the most commonly reported materials, but also difuranyl‐DPP, diselenophenyl‐DPP and dithienothienyl‐DPP‐containing polymers. We discuss the hole and electron mobilities that were reported in relation to structural properties such as alkyl substitution patterns, polymer molecular weights and solid state packing, as well as electronic properties including HOMO and LUMO energy levels. We moreover consider important aspects of ambipolar charge transport and highlight fundamental structure‐property relations such as the relationships between the thin film morphologies and the charge carrier mobilities observed for DPP‐containing polymers.